Communicating across cultures in the globalized context - kaur, Lovleen (Journal of Research in Marketing (ISSN: 2292-9355), 2013)
Cross Cultural Communication can be challenging yet highly rewarding if one comprehends and respects the differences among people of diverse culture, and can go beyond the superficial without any judgment. With the continuing interest and increase in globalization and the diversity in the workplace, cross cultural management has today become an important element of organization life and therefore assumes great relevance. A key to cross cultural change management is to realize that what was acceptable in the past is not necessarily relevant today; the world is constantly converging on some issues and continues to be divergent on many others.